Modelling the cost-effectiveness of introducing the RTS, S malaria vaccine relative to scaling up other malaria interventions in sub-Saharan Africa. Issue 1 (24th January 2017) - Winskill, Peter; Walker, Patrick GT; Griffin, Jamie T; Ghani, Azra C
Abstract : Objectives: To evaluate the relative cost-effectiveness of introducing the RTS, S malaria vaccine in sub-Saharan Africa compared with further scale-up of existing interventions. Design: A mathematical modelling and cost-effectiveness study. Setting: Sub-Saharan Africa. Participants: People of all ages. Interventions: The analysis considers the introduction and scale-up of the RTS, S malaria vaccine and the scale-up of long-lasting insecticide-treated bed nets (LLINs), indoor residual spraying (IRS) and seasonal malaria chemoprevention (SMC). Main outcome measure: The number of Plasmodium falciparum cases averted in all age groups over a 10-year period. Results: Assuming access to treatment remains constant, increasing coverage of LLINs was consistently the most cost-effective intervention across a range of transmission settings and was found to occur early in the cost-effectiveness scale-up pathway. IRS, RTS, S and SMC entered the cost-effective pathway once LLIN coverage had been maximised. If non-linear production functions are included to capture the cost of reaching very high coverage, the resulting pathways become more complex and result in selection of multiple interventions. Conclusions: RTS, S was consistently implemented later in the cost-effectiveness pathway than the LLINs, IRS and SMC but was still of value as a fourth intervention in many settings to reduce burden to the levels set out in the international goals.